STEROIDAL SAPOGENINS 165 STRUCTURE OF THE SAPOGENIN GLYCOSIDES - MARKER, RE; LOPEZ, J (BOTANICA-MEX S. A, TEXCOCO, EM, MEX, 1947)
A study of the possible structure of the sapogenin glycosides has been made.
J OPT SOC AM
Keywords: STEROIDAL SAPOGENINS. 165., STRUCTURE, SAPOGENIN GLYCOSIDES; QUIMICA; QUIMICA INORGANICA; QUIMICA DE LOS PIGMENTOS